Якість упаковок льонотрести при використанні на її збиранні прес-підбирачів - Лімонт, А. С.; Климчук, В. М.; Limont, Anatoly; Klymchuk, Vasily (КНТУ, 2013)
Визначені лінійна маса і довжина шару стебел в рулоні, а також довжина стрічки трести, що піднята з поля і спресована в рулон. Досліджена зміна щільності рулону і пошкодження стебел трести в ньому залежно від відношення лінійної маси шару стебел в рулоні до лінійної маси стрічки трести. The investigation is aimed at increasing the efficiency of mechanized harvesting of the spread rotted straw through improving the use of ПР-1,2Л balers with the pressing chamber with changeable volume and ППР-110 balers with the pressing chamber of invariable volume. The investigation was conducted at the spced of moving units that changed within three levels from 4,26 to 8,90 km/h as well as within three positions of the regulator of the wrapper density which corresponded to its adjustment to the minimal, basic and maximum positions. The author determined the linear weight of the layer in the wrapper and the correlation between the length of the stem layer in the wrapper and the length of the rotter straw belt picked from the field. The character of changes in the linear weight of the stem layer depended on the determined correlation which fluctuated from 0,512 to 1,39. The linear weight of the stem layer amounted from 0,18 to 0,63 kg/m. The changes in the wrapper density and damaged stems in it depending on the relations between the linear weight of the stem layer in the wrapper and the linear weight of the rotted straw belt were specified. The changes in the linear weight of the stem layer in the wrapper depending on the correlation between the length of the stem layer in the wrapper, and the length of the picked rotted straw belt and the density of the wrapper depending on the correlation of the linear weight of the stem layer in the wrapper and the linear weight of the rotted straw belt are described through hyperbola equations with the determined regression coefficients.
The quality of rotted straw wrappers under the use of balers for their harvesting
Keywords: льон-довгунець; треста; збирання; прес-підбирач; використання; рулон; параметри; fiber flax; rotted straw; harvesting; baler; use; wrapper; parameters